Comparison between a Novel Knee Arthrometer and Simultaneous Stress Radiography for the Diagnosis of Complete and Partial Acute Anterior Cruciate Ligament Tears - Junqiao Li; Jiayao Zhang; Mingke You; Xiaolong Yang; Wenjing Ma; Qian Deng; Gang Chen; Xin Tang; Weili Fu; Yan Xiong; Qi Li; Jian Li (Orthopaedic Surgery, 2024)
Objectives The type of ligamentous tear and the degree of knee laxity have important guiding significance for the diagnosis and management of anterior cruciate ligament (ACL) tears. Instrumental measurement is necessary for ACL tears since physical examination and magnetic resonance imaging (MRI) cannot provide an objective and quantitative assessment of knee laxity. This study aimed to compare the application of a novel knee arthrometer and simultaneous stress radiography in differentiating between complete and partial acute ACL tears, and further assess the correlation between the two measurements. Methods A total of 106 patients with complete acute ACL tears and 52 patients with partial acute ACL tears were included in the study. Preoperative arthrometry and simultaneous stress radiography were performed using the Ligs arthrometer at 90, 120, and 150 N to assess side‐to‐side difference (SSD) in anterior knee laxity. The optimal threshold was determined using the receiver operating characteristic (ROC) curve. The area under the ROC curve (AUC) was used to assess the diagnostic value of the measurement. Pearson's correlation coefficient was used to assess the correlation between the two measurements. Results The optimal differential SSD thresholds in the Ligs arthrometer were 2.7 mm at 90 N, 3.8 mm at 120 N, and 4.6 mm at 150 N. Similarly, the optimal differential SSD thresholds in simultaneous stress radiography were 3.8 mm at 90 N, 5.1 mm at 120 N, and 5.6 mm at 150 N. The AUC analysis revealed that the Ligs arthrometer was fairly informative at 90 N (AUC = 0.851), 120 N (AUC = 0.878), and 150 N (AUC = 0.884), and simultaneous stress radiography was highly informative at 90 N (AUC = 0.910), 120 N (AUC = 0.925), and 150 N (AUC = 0.948). Moreover, the AUC of the combined measurements was 0.914 at 90 N, 0.931 at 120 N, and 0.951 at 150 N. A significantly strong correlation was found between the two measurements at 90 N (r = 0.743, p < 0.001), 120 N (r = 0.802, p < 0.001), and 150 N (r = 0.823, p < 0.001). Conclusions The Ligs arthrometer and simultaneous stress radiography proved to be valid diagnostic tools to differentiate between complete and partial acute ACL tears, with a strong correlation between the two measurements in SSD values. Compared with single instrumental measurement, the combination of the two measurements can further improve the diagnostic value in this regard.